Analisis Karakteristik Lanskap Resort Rawa Bunder di Taman Nasional Way Kambas : Analisis Karakteristik Lanskap Resort Rawa Bunder di Taman Nasional Way Kambas - Gunardi Djoko Winarno; Sugeng P Harianto; Bainah Sari Dewi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The importance of research on the Rawa Bunder Resort’s landscape characteristics at Way Kambas National Park (WKPN) is as a basis for area management according to its function in a lowland tropical rain forest ecosystem. The purpose of this study is to find out the current characteristics of landscape include physical and biological characteristics as well as the driving factors for the establishment of good habitat restoration for flora and fauna life. The results showed that the landscape characteristics of the Rawa Bunder Resort consisted of natural forest and open land containing shrubs with almost the same area composition. The position of the forest appears to be united in the middle to the east of the WKNP. The pressure of Imperata fires can threat the existence of forests. If the preventive action is not taken immediately, the forest will decrease in size. The driving factor for the reduction of the forest matrix is ​​the frequent occurrence of forest fires every year. These fires were triggered by humans who intentionally or unintentionally driven by the wind so that it spread widely.